Analisis Pengaruh Communal Activation terhadap Keputusan Membeli untuk Meningkatkan Brand Loyalty (Studi Kasus Teh Botol Sosro Less Sugar) - Gunawan, Annetta (Bina Nusantara University, 2013)
Established in 1974 PT Sinar Sosro is the first bottled ready-to-drink tea producer in Indonesia. In order to fulfill its lovers wherever they are, the newest innovation has been launched, i.e. Teh Botol Sosro Less Sugar, which focuses on diabetics, sportsmen/athletes, and young executives as its target markets. To foster brand loyalty and control the community, PT Sinar Sosro utilizes crowd combo marketing concept, especiallycommunal activation activity that is adjusted with the current New Wave Marketing era, so PT Sinar Sosro can integrate supply and access of Teh Botol Sosro Less Sugar product. The objectives of this research are to analyze the influence of Communal Activation on Buying Decision of Teh Botol Sosro Less Sugar, and to analyze the influence of Communal Activation and Buying Decision on Brand Loyalty of Teh Botol Sosro Less Sugar. The data collection technique used was questionnaire disseminated to the members of Teh Botol Sosro Less Sugar online community, using Likert scale. While the data analysis technique used was Path Analysis. The result of Path Analysis shows the structural equation Y = 0,523 X + 0,8526 Îµ1 which Communal Activation significantly contributes to Buying Decision at 27,3% and Z = 0,552 X2 + 0,229 Y + 0,7141 Îµ2 which Communal Activation and Buying Decision simultantly and significantly contribute to Brand Loyalty at 49%.